1998
DOI: 10.1029/97gl03317
|View full text |Cite
|
Sign up to set email alerts
|

On the Long‐Range transport of air pollutants from Europe to Africa

Abstract: Abstract.The general climatic conditions and the physiographic characteristics of the area around the Mediterranean Sea, result in the formation of a flow pattem which is from North to South during all seasons and mainly during summer. This flow transports polluted air masses from southem Europe towards Africa. This transport is being investigated with the combined use of an atmospheric and a Lagrangian dispersion model. Air pollutants released from sources located in southern Europe were found in the entire t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
85
0
7

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 145 publications
(92 citation statements)
references
References 8 publications
0
85
0
7
Order By: Relevance
“…The transport and the dispersion of air masses reaching the Mediterranean region have been investigated in a number of studies (Kallos et al, 1996a(Kallos et al, , 1998a and in MAMCS as well (Kallos et al, 2000). The results of these studies have shown that plumes (urban or industrial) located near the coast are injected almost entirely within the MBL and stay within it until they reach the southern or southeastern coast of the Mediterranean.…”
Section: Integrated Atmospheric Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The transport and the dispersion of air masses reaching the Mediterranean region have been investigated in a number of studies (Kallos et al, 1996a(Kallos et al, , 1998a and in MAMCS as well (Kallos et al, 2000). The results of these studies have shown that plumes (urban or industrial) located near the coast are injected almost entirely within the MBL and stay within it until they reach the southern or southeastern coast of the Mediterranean.…”
Section: Integrated Atmospheric Measurementsmentioning
confidence: 99%
“…Local thermal circulations are evident across the Mediterranean coastlines while in regions like the Iberian Peninsula more complicated phenomena such as funnelling and multiple layering occur (Millan et al, 1997). In general, during the warm period of the year the flow has a major component from the European coasts towards North Africa in a prevailing direction from N to NW (Kallos et al, 1993(Kallos et al, , 1996a(Kallos et al, , 1997a(Kallos et al, , 1998a). * During the transient seasons, the weather type changes between summer and winter type.…”
Section: Meteorological Patterns Of the Regionmentioning
confidence: 99%
“…Gozo, an island of the Maltese archipelago, is centred in the Central Basin. Subordinate to the large-scale meteorology in the Mediterranean, more meso-scale circulations develop in the Central Basin (Kallos et al 1998). Air masses loaded with pollutants from elsewhere may reach Gozo via the Adriatic and Tyrrhenian seas (Weather in the Mediterranean 1962).…”
Section: Simultaneous Surface Co and So 2 Measurements On Gozomentioning
confidence: 99%
“…Air masses loaded with pollutants from elsewhere may reach Gozo via the Adriatic and Tyrrhenian seas (Weather in the Mediterranean 1962). Air masses transported to the south have a longer sea track on the way to Gozo and North Africa (Kallos et al 1998). Due to the long distance over the Mediterranean sea, the relatively cool sea surface in spring and early summer produces conditions of subsidence and stability in the maritime boundary layer for the air parcels mixed in from the lower troposphere.…”
Section: Simultaneous Surface Co and So 2 Measurements On Gozomentioning
confidence: 99%
See 1 more Smart Citation